2010
DOI: 10.1016/j.clim.2009.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of circulating cells in systemic juvenile idiopathic arthritis across disease activity states

Abstract: Juvenile idiopathic arthritis (JIA) encompasses a group of chronic childhood arthritides of unknown etiology. One subtype, systemic JIA (SJIA), is characterized by a combination of arthritis and systemic inflammation. Its systemic nature suggests that clues to SJIA pathogenesis may be found in examination of peripheral blood cells. To determine the immunophenotypic profiles of circulating mononuclear cells in SJIA patients with different degrees of disease activity, we studied PBMC from 31 SJIA patients, 20 po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
49
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 63 publications
10
49
0
Order By: Relevance
“…Our results could support previous work which has revealed that it is mainly cells of myeloid lineage that participate in the pathogenesis of sJIA [25]. Contradicting our results, Macaubas et al showed a decrease not only in circulating mDCs, but also in pDCs, in patients with active sJIA [26].…”
Section: Hla-dr Positive Cells In Blood and Synovial Fluidsupporting
confidence: 92%
“…Our results could support previous work which has revealed that it is mainly cells of myeloid lineage that participate in the pathogenesis of sJIA [25]. Contradicting our results, Macaubas et al showed a decrease not only in circulating mDCs, but also in pDCs, in patients with active sJIA [26].…”
Section: Hla-dr Positive Cells In Blood and Synovial Fluidsupporting
confidence: 92%
“…Although we have not dissected the functional role of Vg9 + T cells in this subset in particular, our previous results (13) indicate that Vg9 + T cells in the SF of systemic JIA patients can respond to IPP. Taken together with the data of Macaubas et al (27), it could be postulated that during acute flares of systemic JIA, PB Vg9 + T cells migrate to synovium, where they may secrete TNF-a and IFN-g, thus contributing to local inflammation.…”
Section: Discussionmentioning
confidence: 61%
“…To test this postulation, multivariate correlations between the number and function of Treg relevant to autoreactive SF CD4 + T cells and the IPP-dependent responses of SF Vg9 + T cells and disease outcomes will be required to dissect the relative importance of each mechanism in the different subgroups of JIA patients. Interestingly in this regard, Macaubas et al (27) recently reported a downregulation of PB gd T cells, but not of NK cells, during acute exacerbations of systemic JIA specifically, suggesting a unique and specific role of gd T cells during flares of disease in this particular subset of JIA patients. Although we have not dissected the functional role of Vg9 + T cells in this subset in particular, our previous results (13) indicate that Vg9 + T cells in the SF of systemic JIA patients can respond to IPP.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, several reports have shown a continued expression of activation markers while sJIA/AOSD was inactive, thus suggesting that quiescence in sJIA/AOSD may only represent a state of compensated inflammation [91]. This has been derived from observations of elevated levels of monocyte surface markers (CD14 and CD16), serum amyloid A, MIF, and IL-18.…”
Section: The Defective Immunoregulation Hypothesismentioning
confidence: 98%